Pengaruh Penggunaan Limbah Sayuran dalam Ransum Terhadap Performa Produksi Itik Petelur - Emy Saelan; A. S. Nurdin (Fakultas Peternakan, Universitas Padjadjaran, 2018)
The waste vegetables ration the effect to the performance production have been done in cage experiment of Poultry Production Farm in Agriculture Studi Programs Khairun University, Ternate, Maluku Utara. An exsperiment using laying ducks padjadjaran age 46 weeks as 64 ducks. The research used to Completely Randomized Design (CRD) with 4 treatments and 4 replications of, R0 (100% control rations); R1 (5% waste vegetables + 95% control rations); R2 (10% waste vegetables + 90% control rations); and R3 (15% waste vegetables + 85% control rations); and to see the effect of trend pattern of each treatment was done by orthogonal polynomial test. The results (1). Egg production average is R0 (63,04%); R1 (65,37%); R2 (69,79%) and R3 (70,57%) was significantly different (P<0.05); (2). Rations of consumption is R0 (154.36 gram); R1 (153.66 gram); R2 (151.48); and R3 (150.60 gram) was significantly different (P<0.05) between treatment of R0, R2 and R3; (3) Feed conversion rations is R0 (3.46); R1 (3.35); R2 (3.08) and R3 (3.03) was significantly different (P<0.05) R0, R2 and R3, but not significantly different between treatment of R2 and R3 (P>0,05). The use of waste vegetables ration up to 15% in laying ducks rations real increased egg production, improve consumption and feed conversion rations.